Priority Setting for Health Service Coverage Decisions Supported by Public Spending: Experience from the Philippines - John Q. Wong; Jhanna Uy; Nel Jason L. Haw; John Xavier Valdes; Diana Beatriz S. Bayani; Charl Andrew P. Bautista; Manuel Alexander Haasis; Raoul A. Bermejo; Willibald Zeck (Taylor & Francis Group, 2018)
Abstract-Achievement of universal health coverage requires better allocative efficiency in health systems. Countries like the Philippines, however, do not have quality local data for these decisions. We present a method that applies existing global data, e.g., Global Burden of Disease and Disease Control Priorities project, into creating a local priority list of diseases and interventions that may be useful in providing a rational plan for expanding coverage of health services paid by public financing. In the context of the Philippines, this refers to the Department of Health for vertical programs like immunization and disease control, and the Philippine Health Insurance Corporation for inpatient and outpatient health services. We found that the top 48 (or 22%) of diseases account for 80% of total disability-adjusted life years (DALYs), reflecting a well-known concept in management, the Pareto principle. Due to its simplicity and widespread applicability, the Pareto principle facilitated interest in rational priority setting among high-level officials in the Philippine health sector. Priority setting must not be limited to disease burden and cost-effectiveness criteria. Our lists can be used after further deliberation and stakeholder consultation. Priority setting is a complex, value-laden process, and a purely utilitarian approach to prioritization may lead to further deterioration in the health status of vulnerable populations. We recommend that DOH and PHIC set up a joint, independent agency primarily responsible for implementing a sustainable, transparent, and participatory priority-setting process that will advise them on future service coverage expansions.